Evaluation of Cafeteria Diet in Experimental Animal with Plant Extract of Calotropis procera for Obesity Parameter - Nyarko, Richard Owusu; Awuchi, Chinaza Godswill; Kumar, Roshan; Boateng, Edward; Kahwa, Ivan; Boateng, Paul Owusu; Asum, Christian; Saha, Purabi (Journal for Research in Applied Sciences and Biotechnology, 2022)
The function of obesity in an insulin-resistant syndrome associated with hyper insulinemia, hypertension, hyperlipidemia, atherosclerotic diseased illness is vital. Hunger, body weight and lipid profile investigations thus assess Calotropis procera extract in animal models. Adult Wister rats (180-240g) 8 were used in each experimental group. The impact of Cactus Kalahari on hunger, body weight and profile of lipids. (A) Control in weight, (B) obesity and CP+ obesity. Control obesity caused by material of cafeteria cuisine (CD). (CP was induced at (100 mg/kg/day po. for 50 days). Every 10 days, the food give, animal body weight, blood glucose, serum lipids level examined—serum and term tests for Liver Function and Renal Function Tests were checked. Our research has demonstrated that following obesity induction CP pretreatment and administration at 100mg/kg/day p<0.05) have resulted in substantial reductions in food consumption, increased body weight and improved lipid profile, liver enzyme and kidney function tests. Cafeteria food rats also showed considerable growth in body weight gain, famine, lipid profile, hepatic enzymes, and kidney function tests. When administered with a protein-rich food at the same time, the Kalahari extract prevented and reduced body weight gain and profile of lipid alterations in experimental induced obesity(fats) in rats.